Phytoplankton Diversity, Abundance and Toxin Synthesis Potential in the Lakes of Natural and Urban Landscapes in Permafrost Conditions - Sophia Barinova; Viktor A. Gabyshev; Olga I. Gabysheva; Yanzhima A. Naidanova; Ekaterina G. Sorokovikova (Land)
The region of Eastern Siberia that we have been studying is situated in Yakutia in the permafrost area. We studied five lakes of various geneses, located both in the urbanized territory of Yakutsk city and its suburbs and in natural landscapes at a distance from the impacted area. All lakes were found to have high levels of ammonium nitrogen, total phosphorus and total iron. The lakes’ plankton was found to contain 92 species of algae and cyanobacteria. Cyanobacteria in most lakes accounted for 53 to 98% of the biomass. In one of the natural lakes, 95% of the total biomass was Dinoflagellata. Bioindication, statistics and ecological mapping methods revealed correlations between cyanobacterial production intensity, landscape runoff and lake trophic state. Potentially toxic cyanobacteria containing microcystin and saxitoxin synthesis genes were found in four lakes. Our previous studies established that cyanobacterial harmful algal bloom (CyanoHABs) with microcystin production are characteristic only for lakes in urbanized areas that experience the input of nutrients and organic matter due to anthropogenic runoff. This study indicates that CyanoHABs are possible in lakes in natural areas that are permafrost-dune-type lakes according to their genesis. For the first time in the region, potentially toxic cyanobacteria with saxitoxin synthesis genes have been found. Dune-type lakes do not freeze to the bottom during winter due to taliks underneath them, which provides advantages for cyanobacteria vegetation. Dune-type lakes are very common in the permafrost area, so the extent of CyanoHAB’s distribution in this region may be underestimated.